Qualidade nos lucros : efeito combinado da persistência nos lucros com o gerenciamento de resultados - Maria Júnior, Elizeu (2018)
The financial reports constitute a relevant source of information for investors and other agents of the capital market. This thesis is dedicated the analysis of the Persistence in profits and of Earnings management while attributes of the quality of finan